Hubungan Praktik Pemberian Susu Formula Dengan Status Gizi Bayi Usia 0-6 Bulan Di Kecamatan Semarang Timur Kota Semarang - Puji Lestari; - Suyatno; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
The Correlation Between Formula Milk Feeding Practices And Infant Nutritional Status (0-6 Months) In East Semarang District Semarang: Infant nutrition status is condition that influenced by nutrition intake from the food consumed daily such as formula milk feeding, breast milk. Unappropriate formula milk feeding practices from dose, frequency, and sanitation of formula milk serving make nutritional problems can under nutritional, or more nutritional. The purpose of this research was to find out the correlation between formula milk feeding practice and infant nutritional status at age 0-6 months in east Semarang district Semarang. This was descriptive analytical research using cross sectional design. Population in this study was infant at age 0-6 months (218 infants), then taken as many as 97 samples consume formula milk, to take samples using accidental random method. The data analysis used here applied Rank Spearman and Chi Square correlation test with significance value α =0,05 (p<0,05). The result shown the formula milk feeding on average 11,31 gram/serving 12x/day, sanitation formula presenting the average scores of 7 (1-10), nutritional status sampel is good nutritional (52,57%), more nutritional (37,11%), less nutritional (8,25%), under nutritional (2,05%), Results of Spearman and Chi Square test shown there was correlation between frequency, dose of formula feeding practice and nutritional adequacy rate, there was correlation between the sanitation of formula milk serving, baby sitters, with length and frequency of diarrhea, there was correlation between the length and frequency of diarrhea, nutritional adequacy rate, inequality dose with nutritional status. From this study, it can be concluded that there is correlation between formula milk feeding practices and nutritional status of infant age 0-6 months